Cultural and urban city living expectations of knee motion in a Southeast Asian city: implications on total knee arthroplasty outcomes - Tan, Yong Yao; Ang, Ke Xin Magneline; Wong, Ching Yi Aliza; Mehta, Kinjal Vidyut; Loh, Sir Young James (Frontiers in Rehabilitation Sciences, 2025)
BackgroundThe prevalence of knee osteoarthritis in Southeast Asia has increased steadily over the years. When conservative management options fail, total knee arthroplasty (TKA) is a reliable surgical option. Despite over 90% post-operative satisfaction, the high volume of TKAs performed means that even a small percentage of dissatisfied patients holds significance. Dissatisfaction often arises from unmet expectations, which are influenced by cultural and urban factors specific to the region. Surgeons must counsel patients on likely post-operative activities, but limited data on knee range of motion (ROM) for daily tasks in Southeast Asia renders personalised guidance challenging.AimThe primary aim of this study was to evaluate the minimum knee ROM required for daily activities (walking, stair climbing, squatting, kneeling, and sitting cross-legged) in a healthy Southeast Asian urban population. The secondary aim was to determine the association between anthropometric measurements and knee ROM required for the activities. This information is useful in managing patient expectations after TKA.MethodsAn email describing the study was sent to hospital staff to recruit them as volunteers for the study. Enrolled participants were required to be between the ages of 21 and 65 years and capable of providing informed consent. Interested volunteers with a past medical history involving the lower limbs and spine were excluded. Those with a history of lower limb joint pain or back pain within the last 1 year were also excluded. The KINEXCS KIMIA device (KIMIA Recover System, 2022 edition v1.0) was used to measure the knee ROM. The overall characteristics of participants were summarised using descriptive statistics. Anthropometric measurements and their association with knee ROM during the various activities were analysed. Variables with p-values <0.3 in univariate analysis were included in the multivariable analysis.ResultsFifty participants (32 men, 18 women) were enrolled in the study. The average age of participants was 28.5 years (SD 5.57). The average height was 168 cm (SD 0.0870), and the average body mass index was 23.02 kg/m2 (SD 2.82). The average knee ROM requirements for various activities are as follows: walking on flat ground and stair climbing required less than 90°, squatting and kneeling required at least 127°, and sitting cross-legged required 106°. Lower limb length, leg length, and calf circumference were significantly correlated with the knee ROM required to perform the activities.SignificanceThe findings of this study, combined with an understanding of cultural expectations, might prove valuable for counselling and managing patients undergoing TKA in an urban Southeast Asian country.